Teacher social compensation, student peer attitude, and parent perception of inclusion in two high schools - Rabago, Rudolph Arnold A., author (College of Education, University of the Philippines, 2020)
Social inclusion can be divided into two domains: interpersonal relationships and community participation. This study aimed to analyze the concepts of peer attitude, social compensation, and parent perception within the context of these domains. The researcher used a mixed method of using surveys and interviews in two inclusive junior high schools in the Philippines. The peer attitudes of participating students were measured using a quantitative Peer Attitude Scale supported by follow-up interviews on selected students, and a qualitative Teacher Self-report Narrative on Peer Attitude. Then, the social compensation strategies practiced by teachers were measured using a qualitative Teacher Social Compensation Questionnaire. Observations by the researcher provided in a Researcher Observation Logbook gave additional observations on peer attitudes, and the social compensation strategies. For Social Inclusion, a qualitative Admin Social Inclusion Profile was answered supported by a Parent Questionnaire on Social Inclusion. The researcher discovered that the peer attitudes of the participating classes of both inclusive high schools were positive. The scores of both schools on the Peer Attitude Scale were above the 2.50 median on a four point Likert-like scale. Additional information gathered from the qualitative data from teachers, and researcher observations confirmed these findings. Then, the participating teachers identified two to four social compensation strategies practiced in their classes. More so, the researcher observed some of these strategies in use. Finally, the social inclusion program of the schools generated positive feedback on the part of parents. This included an appreciation of the schools' mission vision, and the integration of general education students and Children with Special Needs in one community.